A cross-sectional and longitudinal study of how two intervention methods affect the anxiety, sleep quality, and physical activity of junior high school students under quarantine - Chen, Peng; Chen, Ying; Jin, Shengjie; Lu, Pengcheng (Frontiers in Psychology, 2023)
Purpose: This study investigates levels of anxiety and sleep quality and their association with physical activity in junior high school students under quarantine during the COVID-19 pandemic. It also tests the effectiveness of physical activity and psychological nursing interventions in alleviating anxiety and improving sleep quality. Methods: In July 2021, 14000 home-quarantined junior high school students in Yangzhou City (China) were selected by random cluster sampling to complete an online survey. We then selected 95 junior high school students for an 8-week longitudinal experiment exploring whether the two types of intervention made positive contributions to students’ anxiety, sleep quality, and physical activity. Results: The cross-sectional study revealed that physical activity was significantly related to anxiety and sleep quality. In the longitudinal study, students who underwent the exercise intervention or the psychological nursing intervention experienced significantly improvement in their anxiety level. The exercise intervention also promoted improved sleep quality. Overall, the exercise intervention was more effective than the psychological nursing intervention in reducing levels of anxiety and sleep disorders. Conclusion: During the epidemic period, junior high school students should be encouraged to spend more time engaging in physical activity, and their sleep quality and anxiety should be focused on.